ERECTOR SPINAE PLANE BLOCK AS ADD ON ANESTHETIC TECHNIQUE TO GENERAL ANESTHESIA FOR CHOLECYSTECTOMY - Dimitrovski A; Toleska M; Shosholceva M; Kartalov A.; Stefanovski D; Kuzmanovska B. (Department of Anesthesia and reanimation, Faculty of Medicine, "Ss.Cyril and Methodius", University Skopje Macedonia, 2020)
Open cholecystectomy is a surgical procedure which is followed by severe peroperative and postoperative pain. The use of Erector Spine Plane Block (ESPB) as a part of multimodal analgesia in a patient classified as ASA 4, significantly reduced the need for opiates during the operation, as well as in the postoperative period. Erector spinae plane block provides excellent analgesia and cardio circulatory stability during and after the operation. This block can be used as part of multimodal analgesia.
Keywords: Analgesia; Erector Spinae Plane Block; Open Cholecystectomy